Evaluasi Penerapan Standar Pelayanan Kefarmasian di Puskesmas Bambu Mamuju Berdasarkan Permenkes RI No. 26 Tahun 2020 - Agust Dwi Djajanti; Rusli Rusli; Febriyanti Febriyanti; A. Tenri Ugi; Sainal Edi Kamal (Media Kesehatan Politeknik Kesehatan Makassar, 2025)
In order to improve the quality of health services available to the community, pharmaceutical services at community health centers are an important component in the implementation of health initiatives. Minister of Health Regulation No. 26 of 2020 concerning Standards for Pharmaceutical Services at Community Health Centers, which includes (management of pharmaceutical supplies and disposable medical supplies, clinical pharmacy services, and the facilities or infrastructure required to support pharmaceutical services at community health centers) represents the latest update to the standards for pharmaceutical services at community health centers, which have undergone several revisions to support these objectives. Determining the feasibility of implementing pharmaceutical service standards at the Bambu Mamuju Community Health Center in Mamuju Regency is the objective of this study. Using a checklist and in-depth interviews, this study combines a descriptive approach with an observational strategy. The study was conducted from December 2024 to January 2025. The population in this study was the pharmaceutical services at the Bambu Community Health Center in Mamuju District. The informants used in this study were the pharmacists in charge of the pharmacy at the Bambu Community Health Center. Based on the results of the study, the Bambu Mamuju Community Health Center in Mamuju Regency has implemented pharmaceutical services in accordance with the Bambu Mamuju Community Health Center standards with an average score of 84.2% in the good category, in accordance with Minister of Health Regulation No. 26 of 2020. Clinical pharmacy services at the health center still need improvement, but the management of pharmaceutical supplies, single-use medical devices, facilities, and infrastructure is in line with the technical guidelines for pharmacy service standards. Keywords: Pharmacy Service Evaluation, Health Center, Ministry of Health Regulation No. 26 of 2020, Checklist Sheet